SEJARAH PERKEMBANGAN FILSAFAT: DARI RASIONALITAS YUNANI HINGGA INTEGRASI KEILMUAN ISLAM KONTEMPORER - Darnanengsih; A. Marjuni; Afifuddin Harisah (Pascasarjana IAIN Sorong, 2026)
This study aims to trace the historical development of philosophy from Ancient Greece to contemporary Islam and its relevance to the formation of an integrative paradigm of Islamic knowledge. Using a qualitative approach and historical-philosophical method through library research, the study refers mainly to Marjuni’s Filsafat Pendidikan Islam (2021). The findings reveal that the evolution of philosophy from the 6th century BC to the 21st century AD represents a dialectic between rationality and spirituality. Greek philosophy laid the foundation of rational thought, while classical Islamic philosophy (8th–13th centuries AD) refined it with theological and ethical dimensions. In the modern context, Islamic educational philosophy integrates knowledge, faith, and action through the unity of rationality, morality, and spirituality. Thus, Islamic philosophy is a system of knowledge grounded in tawhid and universal humanity that must be re-actualized to address moral and spiritual crises in the modern era.